The Differential Characteristics Between Severe Fever With Thrombocytopenia Syndrome and Hemorrhagic Fever With Renal Syndrome in the Endemic Regions. (5th November 2019) - Lu, Qing-Bin; Li, Hao; Jiang, Fa-Chun; Mao, Ling-Ling; Liu, Xue-Sheng; Wang, Ning; Zhou, Yong-Yun; Dai, Ke; Yang, Zhen-Dong; Dong, Li-Yan; Cui, Ning; Zhang, Xiao-Ai; et al.
Abstract: An effective differentiation between severe fever with thrombocytopenia syndrome and hemorrhagic fever with renal syndrome was attained by a model considering patients' age, mouse/tick contact, presence of blush, low back pain, diarrhea, enlarged lymph nodes, and white blood cell count.